2009
DOI: 10.1007/s12033-009-9143-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Streptococcus pyogenes and Streptococcus dysgalactiae subsp. equisimilis

Abstract: We developed molecular diagnostic assays for the detection of Streptococcus pyogenes (GAS) and Streptococcus dysgalactiae subsp. equisimilis (SDSE), two streptococcal pathogens known to cause both pharyngitis and more invasive forms of disease in humans. Two real-time PCR assays coupled with an internal control were designed to be performed in parallel. One assay utilizes a gene target specific to GAS, and the other utilizes a gene target common to the two species. Both assays showed 2-3 orders of magnitude im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…To implement the use of improved detection methods with DNA microarrays, the present study evaluated photopolymerization, a novel colorimetric detection method (Kuck and Taylor, 2008;Sikes et al, 2008;Dawson et al, 2009), for genotyping E. coli O157 strains. To provide a proof of concept for testing photopolymerization, a low-density 30-mer DNA oligonucleotide array was constructed to target the E. coli O157 virulence genes eae, per, stx1, and stx2 (Table 1).…”
Section: A Novel Colorimetric Methods For Detection Of Pathogenic E Cmentioning
confidence: 99%
See 4 more Smart Citations
“…To implement the use of improved detection methods with DNA microarrays, the present study evaluated photopolymerization, a novel colorimetric detection method (Kuck and Taylor, 2008;Sikes et al, 2008;Dawson et al, 2009), for genotyping E. coli O157 strains. To provide a proof of concept for testing photopolymerization, a low-density 30-mer DNA oligonucleotide array was constructed to target the E. coli O157 virulence genes eae, per, stx1, and stx2 (Table 1).…”
Section: A Novel Colorimetric Methods For Detection Of Pathogenic E Cmentioning
confidence: 99%
“…For photopolymerization to occur, a streptavidinconjugated photoinitiator is used to specifically label the microarrays that have been hybridized with the biotin-labeled, single-stranded DNA targets (Kuck and Taylor, 2008). After irradiating at a wavelength absorbed by the photoinitiator (l 404 nm), polymer forms exclusively in only a few minutes where the probe sequences were spotted on the microarray (Kuck and Taylor, 2008;Dawson et al, 2009); polymer formation can be observed after staining (Kuck and Taylor, 2008).…”
Section: A Novel Colorimetric Methods For Detection Of Pathogenic E Cmentioning
confidence: 99%
See 3 more Smart Citations